2022
DOI: 10.1093/pm/pnac007
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-Guided Suprazygomatic Nerve Blocks to the Pterygopalatine Fossa: A Safe Procedure

Abstract: Objectives Large-scale procedural safety data on pterygopalatine fossa nerve blocks (PPFB) using a suprazygomatic, ultrasound-guided approach are lacking, leading to hesitancy surrounding this technique. The aim of this study was to characterize the safety of PPFB. Methods This retrospective chart review comprised adults who received an ultrasound-guided PPFB from 01/01/2016–08/30/2020 at the University of Florida. Indication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…1 He unsuccessfully treated the patients over at least 4 years with antihistamines, phenothiazines, H1-antagonists, methysergide, indomethacin, prednisone, propranolol, and lithium carbonate before the pterygopalatine ganglion (PPG) alcoholizations. Similar to more recent studies, 3 4 Devoghel found that the percutaneous suprazygomatic approach to the PPG is the simplest and safest technique, and he achieved a remarkable success rate of 85.8% of patients who went into apparent permanent remission. 1 While the etiopathogeneses of most secondary headaches are generally well understood, 5 that of primary headache disorders (PHDs) still eludes us.…”
Section: Introductionsupporting
confidence: 73%
“…1 He unsuccessfully treated the patients over at least 4 years with antihistamines, phenothiazines, H1-antagonists, methysergide, indomethacin, prednisone, propranolol, and lithium carbonate before the pterygopalatine ganglion (PPG) alcoholizations. Similar to more recent studies, 3 4 Devoghel found that the percutaneous suprazygomatic approach to the PPG is the simplest and safest technique, and he achieved a remarkable success rate of 85.8% of patients who went into apparent permanent remission. 1 While the etiopathogeneses of most secondary headaches are generally well understood, 5 that of primary headache disorders (PHDs) still eludes us.…”
Section: Introductionsupporting
confidence: 73%
“…This delay can be attributed to educational efforts, additional time for procedural timeouts, and coordination between teams before and after the procedure. While the ultrasonography approach may only need minimal readily available equipment in pediatric operating rooms and can be done within 10 minutes, the alternative landmark SZMN block uses less than 2 minutes . Increases in operating room time may mean reserving this technique for subsets of patients that will have maximal benefit.…”
Section: Discussionmentioning
confidence: 99%
“…While the ultrasonography approach may only need minimal readily available equipment in pediatric operating rooms and can be done within 10 minutes, the alternative landmark SZMN block uses less than 2 minutes. 9,41,74 Increases in operating room time may mean reserving this technique for subsets of patients that will have maximal benefit.…”
Section: Limitationsmentioning
confidence: 99%
“…were utilized at least occasionally by nearly one of ve respondents. While most published data on any of these treatments are based on case reports or smaller case series, experience with pterygopalatine fossa blocks, occipital nerve blocks and acupuncture have been reported with potentially promising results [15,16,40,41] and may offer potential additions to the multi-drug regimens that are most commonly employed. Providers considering such alternative strategies were more likely based in North Americalikely a re ection of the regional shift from opioid-based analgesia-and were more likely to be considered in a setting where the intensive care team was responsible for analgesia.…”
Section: Alternative Analgesic Strategiesmentioning
confidence: 99%
“…More recently, multimodal pharmacotherapy with agents such as gabapentinoids, magnesium infusions, corticosteroids, and utilization of nerve blocks have been reported [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%